Societies and Spaces in Contact - Bufon, Milan,Malloy, Tove H.,Williams, Colin (Peter Lang GmbH, 2021)
This volume speaks to the inter-disciplinary issues related to divergence and convergence processes and situations in contact regions, offering fresh and innovative insights from the crucial Central-Eastern European area where conflict and coexistence potentials seem to best represent the
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Electronic books; Mehrsprachigkeit; Minderheitenpolitik; Ethnische Beziehungen; Multikulturelle Gesellschaft; Soziale Integration